Characteristics of patients with somatoform pain disorder - Lena Barth; Linda Baumbach; André Hajek; Lutz Götzmann; Katrin Feiks; Michael Rufer; Kyrill Schwegler; Bianca Schwennen; Kirstin Bernhardt; Uwe Wutzler; Paul Kaiser; Lutz Wittmann; et al. (Journal of General and Family Medicine)
Abstract Background Patients with somatoform pain experience physical pain that cannot be attributed to any underlying medical or physiological cause, and it is often thought to be related to psychological factors. Health professionals encounter difficulties identifying this specific type of chronic pain, leading to suboptimal treatment strategies. Therefore, we aimed to describe the characteristics of patients with somatoform pain, to support the identification of affected patients. Methods We collected and analyzed a cross‐sectional survey data from 200 patients with somatoform pain admitted to one of three psychosomatic centers in Germany between August 2013 and July 2014. The survey contains 10 different categories, all of them referring to pain‐related topics. Within the survey, we analyzed validated as well as non‐validated questionnaires. Here, we present the following five: Personal data, Body: Pain perception, Cognition: Pain processing, Pain behavior, and Physical complaints. Results Our results highlight that most patients with somatoform pain experience it in several body parts and as persisting, lasting >12 h/day (50%), and constantly changing (71%). Furthermore, patients indicate feelings of helplessness, by agreeing to the expressions the pain controls me (70%). Finally, we found that pain is predominantly seen as suffering, failing to convey emotional pain, despite cognitively acknowledging the dependency of emotional and physical pain. Conclusion The study identified specific and distinctive characteristics in the emotional and behavioral responses of patients with somatoform pain, potentially distinguishing them from other patients with chronic pain.